(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Jane Austen (16December 1775 – 18 July 1817) was an English novelist whose works of romantic fiction, setamong the landed gentry,earned her a place as one of the most widely read writers in Englishliterature. Her realism, biting irony and social commentary have gained herhistorical importance among scholars and critics. The social milieu of Austen’sRegency England was particularly stratified, and class divisions were rooted infamily connections and wealth. In her work, Austen is often critical of theassumptions and prejudices of upper-class England. She distinguishes betweeninternal merit (goodness of person) and external merit (rank and possessions).Though she frequently satirizes snobs, she also pokes fun at the poor breedingand misbehavior of those lower on the social scale. Nevertheless, Austen was inmany ways a realist, and the England she depicts is one in which socialmobility is limited and class-consciousness is strong.